Islamic Reasoning and Indigenous Counseling in Kidung Rumeksa Ing Wengi by Sunan Kalijaga (An Epistemological Study) - Rochman, Kholil Lur; Budiantoro, Wahyu; Ardiansyah, Ardiansyah; Hasni, Hasni (ADDIN, 2025)
The research aims to identify the relationship between Islamic reasoning and indigenous counseling framework within the Javanese hymn, Kidung Rumeksa Ing Wengi. The investigation is motivated by the increasing incorporation of contemporary counseling approaches based on local wisdom traditions, which reflects a significant integration of cultural-traditional heritage and public mental health. This research employed a qualitative method with a literature study approach. Data was obtained through a systematic examination of scholarly literature, including books, journals, and manuscripts of Kidung Rumeksa Ing Wengi. Meanwhile, data analysis uses descriptive qualitative to discuss three stanzas in Kidung Rumeksa Ing Wengi that have correlations with indigenous counseling. The results of this study indicate that three core indigenous counseling values are embedded in Kidung Rumeksa Ing Wengi, including perception, human nature, and mindfulness. All three values are often used as an established intervention approach in contemporary therapeutic or counseling practices. Meanwhile, from an Islamic perspective, Kidung Rumeksa Ing Wengi can also be positioned as a prayer and a psychotherapeutic instrument for enhancing mental health and individual self-balance.